2022
DOI: 10.3389/fonc.2022.789198
|View full text |Cite
|
Sign up to set email alerts
|

Practical Model to Optimize the Strategy of Adjuvant Postmastectomy Radiotherapy in T1-2N1 Breast Cancer With Modern Systemic Therapy

Abstract: PurposeThe effect of adjuvant irradiation after mastectomy in early-stage breast cancer patients remains controversial. The present study aims to explore the clinical benefit obtained from adjuvant radiotherapy among post-mastectomy pT1-2N1 breast cancer patients who received adjuvant modern systemic therapy.MethodsMedical records of consecutive patients with pT1-2N1 breast cancer who received mastectomy in our institution between January 2009 and December 2016 were retrospectively reviewed. High-risk features… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 32 publications
0
4
0
2
Order By: Relevance
“…Therefore, one size did not fit all, and not all BCs could benefit from comprehensive RNI. Based on our established clinical risk model for N1 breast cancer ( 45 , 46 ), our group initiated a prospective randomized clinical trial to investigate whether a part of pN1 breast cancer patients could be safely omitted from IMNI by using a clinical-genomic model, and the trial was under recruiting(NCT04517266). The preliminary results of enrolled 75 patients showed that among clinically high-risk pN1 BC, which is defined as having at least two of the five clinical risk factors (age≤40, three positive LN(lymph node), T2 stage, grade 3, and Ki-67 index≥14%), 70% of them present with genomic high risk, and 30% present with genomic low risk, and whether those clinical high-risk but genomic low-risk BC patients could be omitted from IMNI still needs long-term follow-up of our research ( 47 ).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, one size did not fit all, and not all BCs could benefit from comprehensive RNI. Based on our established clinical risk model for N1 breast cancer ( 45 , 46 ), our group initiated a prospective randomized clinical trial to investigate whether a part of pN1 breast cancer patients could be safely omitted from IMNI by using a clinical-genomic model, and the trial was under recruiting(NCT04517266). The preliminary results of enrolled 75 patients showed that among clinically high-risk pN1 BC, which is defined as having at least two of the five clinical risk factors (age≤40, three positive LN(lymph node), T2 stage, grade 3, and Ki-67 index≥14%), 70% of them present with genomic high risk, and 30% present with genomic low risk, and whether those clinical high-risk but genomic low-risk BC patients could be omitted from IMNI still needs long-term follow-up of our research ( 47 ).…”
Section: Discussionmentioning
confidence: 99%
“…The role of PMRT in whole pT1‐2N1M0 BC patients and the heterogenous impact of PMRT in patient subsets remain controversial. 24 Previous studies demonstrated that PMRT had no effect on prognosis in pT1‐2N1M0 BC patients, 25 , 26 but other studies concluded that PMRT was valuable. 27 , 28 , 29 The EBCTCG meta‐analysis clarified the benefit of PMRT in node‐positive BC patients and confirmed that radiotherapy reduced locoregional recurrence, overall recurrence and BC mortality in 1314 patients with 1–3 positive nodes.…”
Section: Discussionmentioning
confidence: 99%
“…В китайском исследовании 2022 г. за 7-летний период наблюдения изучена группа пациенток РМЖ pT 1-2 N 1 (n=548), которым выполнена мастэктомия [13]. Признаки высокого риска рецидива включают в себя возраст пациентки, количество положительных лимфатических узлов, Т-стадию и индекс Ki67.…”
Section: влияние лучевой терапии на рецидив рака молочной железыunclassified
“…Таким образом, ЛТ значительно улучшила безрецидивную выживаемость у пациентов РМЖ pT 1-2 N 1 с высоким риском, но не у пациентов с низким риском [13].…”
Section: влияние лучевой терапии на рецидив рака молочной железыunclassified